Roles of Type 1 Insulin-Like Growth Factor (IGF) Receptor and IGF-II in Growth Regulation: Evidence From a Patient Carrying Both an 11p Paternal Duplication and 15q Deletion - Giabicani, Eloïse; Chantot-Bastaraud, Sandra; Bonnard, Adeline; Rachid, Myriam; Whalen, Sandra; Netchine, Irène; Brioude, Frédéric (Frontiers in Endocrinology, 2019)
We report an original association of complex genetic defects in a patient carrying both an 11p paternal duplication, resulting in the double expression of insulin-like growth factor 2 (IGF2), as reported in Beckwith-Wiedemann syndrome, and a 15q terminal deletion, including the type 1 IGF receptor gene (IGF1R), resulting in haploinsufficiency for this gene. The patient was born with measurements appropriate for her gestational age but experienced growth retardation in early childhood, allowing a better comprehension of the IGF system in the pathophysiology of growth. It is possible that IGF-II plays a key role in fetal growth, independently of IGF1R signaling, and that its role is less important in post-natal growth, leaving IGF-I and growth hormone as the main actors.